A two‐step method using air plasma and carbodiimide crosslinking to enhance the biocompatibility of polycaprolactone. Issue 6 (14th May 2016) - Sahapaibounkit, Paramaporn; Prasertsung, Isarawut; Mongkolnavin, Rattachat; Wong, Chiow San; Damrongsakkul, Siriporn
Abstract: In this study, polycaprolactone (PCL) film, a high potential material used in biomedical applications, was treated by air plasma prior to a conjugation by carbodiimide cross‐linking with various types of proteins, including type A gelatin, type B gelatin, and collagen hydrolysate. The properties of modified PCL films were characterized by X‐ray photoelectron spectroscopy (XPS), contact angle measurement, and atomic force microscopy. The XPS results showed that oxygen and nitrogen atoms were successfully introduced on the air plasma‐treated PCL surface. Primary amine was found on the air plasma‐treated PCL films. All proteins were shown to be successfully cross‐linked on air plasma‐treated PCL films. The wettability and roughness of protein‐conjugated PCL films were significantly increased compared to those of neat PCL film. In vitro biocompatibility test using L929 mouse fibroblast showed that the attachment percentage and spreading area of attached cells on all protein‐conjugated PCL films were markedly increased. Comparing among modified PCL films, no significant difference on the attachment of L929 on modified PCL films was noticed. However, the spreading areas of cells after 24 hours of culture on type A gelatin‐ and type B gelatin‐modified PCL surfaces were higher than that on collagen hydrolysate‐modified surface, possibly related to the lower percentage of amide bond on collagen hydrolysate‐conjugated surface compared to those on both gelatin‐conjugated PCL ones. This indicated that the two‐step modification of PCL film via air plasma and carbodiimide cross‐linking with collagen‐derived proteins could enhance the biocompatibility of PCL films. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1658–1666, 2017.